2019
DOI: 10.1002/mgg3.1049
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in PDLIM5 are rare in dilated cardiomyopathy but are emerging as potential disease modifiers

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: A causal genetic mutation is found in 40% of families with dilated cardiomyopathy (DCM), leaving a large percentage of families genetically unsolved.This prevents adequate counseling and clear recommendations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Proteomic analysis of EPB41L5-enriched IACs indicated that EPB41L5 facilitates the recruitment of myosin-II-dependent adhesion components such as ACTN4 and PDLIM5, thereby modulating the repertoire of individual IACs (Figure 6). PDLIM5 belongs to the enigma protein subfamily and contains an N-terminal PDZ domain as well as C-terminal LIM-domains, which enable linkage to a-Actinin and other proteins (Verdonschot et al, 2020). More recently, PDLIM5 and a-Actinin have been implicated in force transmission and mechano-transduction signaling at IACs (Elbediwy et al, 2018;Ajeian et al, 2016;Meacci et al, 2016;Feng et al, 2018;Roca-Cusachs et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis of EPB41L5-enriched IACs indicated that EPB41L5 facilitates the recruitment of myosin-II-dependent adhesion components such as ACTN4 and PDLIM5, thereby modulating the repertoire of individual IACs (Figure 6). PDLIM5 belongs to the enigma protein subfamily and contains an N-terminal PDZ domain as well as C-terminal LIM-domains, which enable linkage to a-Actinin and other proteins (Verdonschot et al, 2020). More recently, PDLIM5 and a-Actinin have been implicated in force transmission and mechano-transduction signaling at IACs (Elbediwy et al, 2018;Ajeian et al, 2016;Meacci et al, 2016;Feng et al, 2018;Roca-Cusachs et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The largest number of isoformswitching genes were found between the infarct and the remote zones (Figure 4B). Among them, we found PDZ and LIM domain protein 5 (Pdlim5), a gene encoding for a protein that localizes to the Z-disk by binding to α-actinin, and which has been implicated in dilated cardiomyopathy (Verdonschot et al, 2020) and in heart failure with preserved ejection fraction (Soetkamp et al, 2021). Pdlim5 has several splice variants, clustered into long and short isoforms, which are dynamically regulated during heart development (Yamazaki et al, 2010).…”
Section: Scnast Reveals the Spatial Isoform Diversity Of The Myocardi...mentioning
confidence: 99%
“…This suggests that the final phenotype is influenced by modifier genes and environmental factors. Among the modifier genes involved in this variability, both protein-coding variants and variants located within enhancers have been described as altering the phenotypic expression of cardiomyopathy-causing mutations [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%